SOCIALIZATION OF TOURISM WORK METHOD AS A MODERN LEARNING MEDIA IN SMA PGRI KABUPATEN LAHAT - Diana Widhi Rachmawati; Erma Yulaini; Ida Suryani; Imelda Ratih Ayu; Barkudin; Ana Theriana; Diana Luspa (LEMBAGA PENELITIAN, PENGABDIAN PADA MASYARAKAT, PENINGKATAN AKTIVITAS INSTRUKSIONAL, PENINGKATAN DAN PENJAMINAN MUTU UNIVERSITAS ISLAM MAJAPAHIT, 2021)
Basically, the subject matter taught in schools, especially SMA PGRI Lahat Regency, in subjects is still minimal in enrichment material, especially in lessons at school. So that the results of renewable lecturers' research can be used as additional material through socialization with teachers and students. The theme of this activity is